Transformative practices: Imagining and enacting relationships in the context of resource development, the Argyle case. (6th August 2013) - Doohan, Kim
Abstract: Failure to recognise or acknowledge and respond to local cultural manifestations of Indigenous peoples' attempts to maintain or reassert themselves in spaces of intercultural engagement in resource management denies the power of their own cultural foundations and principles. This paper reviews experience of informal negotiations at the Argyle Diamond Mine in Western Australia. It argues that giving careful consideration to specific cultural practices and processes associated with place and the social relations these practices engender facilitates development of transforming practices that change outcomes.